HUBUNGAN ANTARA KADAR ZINK (Zn) SERUM DENGAN DEFISIT NEUROLOGIS PADA PASIEN STROKE ISKEMIK AKUT - HASTUTI, MURNI SRI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Stroke causes the highest deaths of non-communicable disease 15.4% in Indonesia. Malnutrition is often found in cases of acute stroke and is associated with poor clinical presentations. One form of malnutrition is micronutrients deficiency such as zinc. In cases of acute infarction stroke serum zinc levels lower than in Trancient ischemic attack. This study aims to determine the correlation between serum zinc levels with neurologic deficits of acute ischemic stroke patients. The method of this study was cross-sectional. Subjects were patients admitted to the neurological ward and stroke unit during August 2013 until April 2014 were diagnosed with acute ischemic stroke who included into inclusion criteria. We analysed the data using chi square test and fisher test on bivariate analysis followed by multivariate logistic regression analysis. Total subjects that match to the inclusion criteria were 72 subjects. Forthy five subjects had serum zinc level less than or equal to 89 μg /dl and 27 subjects had level of serum zinc more than 89 μg/dl. While 24 subjects had NIHSS score more than 8 and 48 subjects had NIHSS score less than or equal to 8. In bivariate analyzes serum zinc levels less than or equal to 89 μg/dl significantly associated with NIHSS score of more than 8 (PR= 4,6; 95%CI 1,367-15,484; p= 0,01) and in the multivariate analysis showed a statistically significant (RP= 5,987; 95%CI 1,531-23.41; p= 0,01). Other variables that were significantly associated with neurological deficits were history of hypertension, nutritional status and rate of leucocytes on hospital admission. The conclusion of this study was that low zinc level was associated with neurological deficits characterized by a high NIHSS scores.